Procedural Guaranteeing of Tenants Rights in Case of Land Use for Farming - V. V. Nezhevelo (Bulletin of Kharkiv National University of Internal Affairs)
The article is primarily aimed at the settlement of practical problematic aspects of realizing the procedural protection of the rights of the participants of leasehold land legal relationships.